Development of CapCut Assisted Learning Video Media on Blood Circulatory System Material at MAN Tapanuli Selatan - Anggun Winda Sari Harahap; Almira Amir; Misahradarsi Dongoran (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The research is motivated by the suboptimal use of video learning media, which does not meet the need for engaging, easily understandable, and relevant learning media that align with the current visual and digital learning habits of students. The learning media used are still not optimal, resulting in low student learning outcomes. This research was conducted with the aim of developing valid, practical, and effective learning video media using the CapCut application on the topic of the human circulatory system for 11th-grade students. The method used in this research is development research (RD) with the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The subjects in this study were 30 students from class XI-7 for the 2024/2025 academic year. The data collection instrument was in the form of validation questionnaires from media, material, and language experts. The questionnaire measuring practicality was distributed to biology teachers and students, while the effectiveness was measured using a pretest-posttest. Data were analyzed descriptively using both quantitative and qualitative methods. The research results show that the developed video media has a validity level from media experts of 98.08% (very valid category), material experts of 92.5% (very valid category), and language experts of 100% (very valid category). Additionally, the response from teachers was 89.58% and the response from students was 93.5% (very practical category). The results of the effectiveness test using student test scores showed a pretest percentage of 67.26% and a posttest percentage of 84.6%. To see theimprovement in student learning outcomes, the N-Gain was calculated with a percentage of 50.99%, categorized as quite effective. Therefore, this CapCut-based learning video media can be used as an effective alternative media in the Biology learning process, especially on the topic of the human circulatory system.